LEGAL CERTAINTY IN THE IMPLEMENTATION OF THE TRANSFER FROM ANALOG CERTIFICATE MEDIA TO ELECTRONIC CERTIFICATE : LEGAL CERTAINTY IN THE IMPLEMENTATION OF THE TRANSFER FROM ANALOG CERTIFICATE MEDIA TO ELECTRONIC CERTIFICATE - Iriantoro, Agung (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
Analog certificates have traditionally served as physical proof of land ownership and proved a sufficient degree of legal certainty. However, with advance in technology and digitalization, the government through Regulation of the Minister of Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 1 of 2021, later replaced by Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 3 of 2023 concerning Issuance of Electronic Documents in Land Registration Activities has sought to provide easier access to the land registration and management process. E-certificates offer easier access to land registration and management processes. Nevertheless, this regulatory shift raises legal questions regarding the status of analog and electronic certificates, as well as the broader need for regulatory harmonization. This research adopts a normative legal approach examining legal literature and secondary data (library research). The finding indicate that electronic certificates offer significant advantages, including easier access, enhanced data security, and greater transparency in registration and data management. The process of media transfer involves verification of both physical and legal data by the National Land Agency, with the Land Deed Officials playing a crucial role in ensuring the validity and legality of such data. Ultimately, digital transformation is necessary to overcome long-standing issues within the land registration system. The transition from analog certificates to electronic certificates represents a strategic step toward modernizing land administration by integrating legal and technological dimensions, thereby creating an efficient, secure, and reliable system.